2018
DOI: 10.1021/acsomega.8b01960
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Triazole-Substituted Quinazoline Hybrids for Anticancer Activity and a Lead Compound as the EGFR Blocker and ROS Inducer Agent

Abstract: A series of triazole-substituted quinazoline hybrid compounds were designed and synthesized for anticancer activity targeting epidermal growth factor receptor (EGFR) tyrosine kinase. Most of the compounds showed moderate to good antiproliferative activity against four cancer cell lines (HepG2, HCT116, MCF-7, and PC-3). Compound 5b showed good antiproliferative activity (IC50 = 20.71 μM) against MCF-7 cell lines. Molecular docking results showed that compound 5b formed hydrogen bond with Met 769 and Lys 721 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Banerji et al synthesized a series of triazole-substituted quinazoline hybrid analogues and evaluated their anti-cancer effect against HCT116 (human colorectal cancer cell line), HEPG2 (human liver cancer cell line), MCF-7 (human breast cancer cell line), and PC-3 (human prostate cancer cell line). 76 The preliminary SAR of erlotinib and lapatinib (EGFR inhibitors) revealed that the presence of 5-aminoquinazoline moiety was helpful for EGFR inhibition. The triazole scaffold has also been previously reported due to its anti-cancer activity via various mechanisms.…”
Section: Anti-cancer Hybridsmentioning
confidence: 99%
“…Banerji et al synthesized a series of triazole-substituted quinazoline hybrid analogues and evaluated their anti-cancer effect against HCT116 (human colorectal cancer cell line), HEPG2 (human liver cancer cell line), MCF-7 (human breast cancer cell line), and PC-3 (human prostate cancer cell line). 76 The preliminary SAR of erlotinib and lapatinib (EGFR inhibitors) revealed that the presence of 5-aminoquinazoline moiety was helpful for EGFR inhibition. The triazole scaffold has also been previously reported due to its anti-cancer activity via various mechanisms.…”
Section: Anti-cancer Hybridsmentioning
confidence: 99%
“…Banerji, B., et al synthesized A series of triazole-substituted quinazoline hybrid molecules as anticancer agents. The results showed that compound (25) has moderate to good antiproliferative effects against four different cell lines HCT116, HepG2, PC-3, and MCF-7 (Banerji, Chandrasekhar et al 2018).…”
Section: Quinazoline Containing Triazolo Moietymentioning
confidence: 99%
“…Banerji et al . have synthesized a range of triazole‐substituted quinazoline hybrid compounds by this procedure that sodium azide which dissolved in water was dropwise added to the solution of product 99 in THF at 0 °C and was then stirred at room temperature.…”
Section: 4‐disubstituted‐123‐triazoles As Anti‐cancer Agentsmentioning
confidence: 99%